Factors influencing referral delay of cancer patients to an oncology unit in the Southern Region of Saudi Arabia - Al Zahrani, Ali M; M Ali, Hatim; A Ahmed, Shaza; M Abdelakher, Ahmed; Al Zahrani, Asma A; Bakhribah, Hatoon (Journal of Community Medicine and Health Solutions, 2021)
Introduction: Cancer treatment and prognosis depend heavily on early detection. Survival in the early stages is excellent for almost all types of cancer. Unfortunately, in Saudi Arabia, a large number of cancer patients present with advanced disease, resulting in a poor prognosis. There are three levels of delay in the management of cancer patients. The first level is the time between the first cancer-related symptoms and the presentation to the health facility, the second level is from the presentation to the diagnosis, and the third level is between the diagnosis and the treatment. This study aims to determine if there is a delay, at what level and to study the factors causing such delays. Materials and methods: Two hundred cancer patients who presented to the Armed Forces Hospital Southern Region, Oncology Department, were interviewed from January 1st to June 30th, 2018. The interviews were conducted by trained physicians familiar with the questionnaire’s contents. The questionnaire consisted of four sections: a demographic section and three more sections to identify factors causing the delay at the three levels from the patients’ perspectives. All data were analyzed using the SPSS version 20.0. Results: The mean patient age was 63 years. A total of 112 patients were female and 88 were male. The most common cancer type was breast cancer (27.5%). Among the patients, 61% were illiterate and 25.5% had elementary school degrees, 86% expressed little or no general medical knowledge about cancer. More women than men paid attention to cancer symptoms (70% vs. 54%). 75% of the patients presented to the first health facility after 2 months from the first appearance of symptoms (level 1 delay). Only 2% of the patients presented within one week. 50% of the patients received a diagnosis after visiting two health facilities. All patients were diagnosed at hospitals. 40% of patients used alternative medicines, 70% of whom thought this was the cause of their delayed presentations. 67% had their diagnosis confirmed within one month (level 2 delay), and 66% started their definitive treatment within one month (level 3 delay). 75% of the patients blame themselves for the delay. Educational level (p = 0.03), knowledge about cancer (p < 0.01), and the use of complementary and alternative medicines (CAM) (p = 0.01) were significantly associated with delayed presentation of patients to the health facility. Conclusion: There is a delay in the presentation of cancer patients (level 1) in the southern part of Saudi Arabia. Educational level, knowledge of cancer symptoms, and use of complementary and alternative medicines are the main causes. There were no delays in diagnosis and start of treatment (level 2,3).